Unrelated Donor Marrow Transplantation for a Case of Chiédiak-Higashi Syndrome with Hereditary Elliptocytosis (Ibrahim Medical College Journal, 2009)
Key words: Chiédiak-Higashi Syndrome; Elliptocytosis Ibrahim Med. Coll. J. 2008; 2(1): 28-31 doi: 10.3329/imcj.v2i1.2929